Hematological responses to iron-folate supplementation and its determinants in pregnant women attending antenatal cares in Mekelle City, Ethiopia - Belay, Ezra (PLoS One, 2018)
OBJECTIVE: To characterize anemia and evaluate hematological responses to universal iron-folic acid (IFA) supplementation in Ethiopian pregnant women. METHOD: A hospital- based prospective follow up study was done between December 2016 and June 2017. Hematological profiles were measured in pregnant women before and after a minimum of one-month IFA supplementation. Mean values and abnormal proportions of hematological profiles were compared before and after supplementation using paired t-test and McNemar test, respectively. Univariate and multivariate analysis were used to analyze the association between independent variables and poor treatment responses. RESULT: Lack of adequate hemoglobin response was found in 48.5%(95/196) of the participants. Prevalence of anemia and low hematocrit value were decreased significantly after IFA supplementation (p = 0.002, and p = 0.001, respectively). Normocytic hypochromic anemia was the commonest form of anemia found in this study followed by normocytic normochromic anemia. There was no statistically significant association between poor hemoglobin responses and all studied factors such as educational level, household size, parity, recent illness, stage of pregnancy, coffee consumption, and duration of iron treatment. CONCLUSION: Our study revealed poor hemoglobin responses in nearly half of the study participants and a high proportion of anemias morphologically atypical of iron deficiency anemia. There is a need to consider anemia attributable to etiologies other than an iron deficiency in anemia intervention programs.